2004
DOI: 10.1111/j.1538-7836.2004.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX polypyrimidine tract mutation analysis using mRNA from peripheral blood leukocytes

Abstract: To cite this article: Van de Water NS, Tan T, May S, Browett PJ, Harper P. Factor IX polypyrimidine tract mutation analysis using mRNA from peripheral blood leukocytes. J Thromb Haemost 2004; 2: 2073-5.The production of illegitimately transcribed mRNA from peripheral blood leukocytes and its use for mutational analysis of many tissue-specific genes has been known for 15 years [1]. Two recent publications in this journal by Green et al. and Cutler et al. [2,3] have, however, highlighted the difficulty in using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This region is important to initially recognize ASS through U2AF protein complex binding [Zorio and Blumenthal, ]. It has been shown several times that its deletions or even single point substitutions can hamper normal splicing of the affected gene, most likely due to restraint binding of U2AF larger subunit [Van de Water et al, ; Carboni et al, ; Dardis et al, ]. It would correspond with Sroogle predictions showing a marked decrease of PPT quality in terms of score and percentile between a set of more than 50,000 constitutive exons.…”
Section: Discussionmentioning
confidence: 88%
“…This region is important to initially recognize ASS through U2AF protein complex binding [Zorio and Blumenthal, ]. It has been shown several times that its deletions or even single point substitutions can hamper normal splicing of the affected gene, most likely due to restraint binding of U2AF larger subunit [Van de Water et al, ; Carboni et al, ; Dardis et al, ]. It would correspond with Sroogle predictions showing a marked decrease of PPT quality in terms of score and percentile between a set of more than 50,000 constitutive exons.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that a missense mutation might introduce a cryptic splice site [13], or interfere with the exonic splicing enhancer motifs [14,15]. Because of the difficulty in recovering illegitimately transcribed mRNA from peripheral blood leucocytes [16–18], we were unable to ascertain whether the absence of the protein in patients who presented FIX:Ag level below 1% was due to an incorrect mRNA splice or if an altered and/or unstable protein had been transcribed. Therefore, we excluded these patients from the protein model inspection.…”
Section: Discussionmentioning
confidence: 99%
“…It appears challenging in some instances to obtain full-length F9 cDNA from peripheral leukocytes. Sarkar et al analyzed F9 mRNA by using single-strand conformation polymorphism, but did not highlight difficulties in obtaining mRNA [32], and van der Water et al [33] sequenced leukocyte exon 2-4 transcript in wild-type and mutant to identify an intron 2 splice mutation. Green et al could only obtain a partial transcript of exons 7-8 from leukocytes, in contrast to liver-derived F9 mRNA, where the entire transcript was present [34]; similarly, Cutler et al [35] reported leukocyte transcripts from exons 1-2 and 7-8, but not from central F9 exons.…”
Section: Analysis Of F9 Mrnamentioning
confidence: 99%